CEO to the Rescue: Residential Proximity of Private Firm CEOs and the Evolution of Corporate Profitability - Woo Jin Kim; Dong-Ryung Yang (KDI Journal of Economic Policy, 2016)
This paper documents how the net profit margin of private firms improves when the CEOs of the companies relocate their primary residence to be closer to the corporate headquarters. By reviewing 127 Korean non-public companies belonging to 66 private business groups, we find that the top managers move closer to the headquarters when the profitability of the firms has recently deteriorated. A one basis point decline in the margin causes CEOs to relocate their homes approximately two kilometers closer to their corporate headquarters. The profit margin rebounds after their relocation. This finding implies that physical proximity can serve as a proxy for personal commitment.
Keywords: G30; G34; G39; 330; CEO; Corporate Governance; Geographic; Commitment